The Protection of Human Rights in Steven Spielberg's Schindler's List: A Sociological Perspective - Ranata, Lintang; M. Thoyibi (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research aims to describe how the depiction of human rights protection by Oskar Schindler is based on the movie Schindler's List by Steven Spielberg. This research aims to answer several questions that formulate the problem, namely the indicators of human rights protection, the depiction of human rights protection, and the director's reason for highlighting human rights protection in the movie Schindler's List. Later, this research will provide answers regarding the protection of human rights that occur through the film that has been determined as the object of research. This type of research is a literature study. Researchers used the document analysis method to collect data and used copy-and-paste and image-capturing techniques. The findings of this study show that there are five indicators of human rights protection, namely: (1) Employee Recruitment, (2) Making New Policies, (3) Buying the Jews, (4) Defending His Workers, (5) Transferring the Jews into Brünnlitz. The protection of human rights is depicted through characterization, setting, event, and style. As an American-Jewish, Spielberg strives to convince the audiences not to forget the history of the Holocaust.